Attitude adjustments after global health inter-professional student team experiences. Issue 16 (April 2020) - Skolka, Michael; Hennrikus, William L.; Khalid, Muhammad; Hennrikus, Eileen F.
Abstract : Abstract: How medical inter-professional (IP) education should be introduced to students is still a matter of research. We evaluated IP student attitudes before and after a busy "hands-on" clinical experience. During 3 separate trips, first/second year medical and physician assistant students and third/fourth year nursing students traveled to Central America to work together for 1 week in an underserved clinical setting. Student opinions on inter-professional education were obtained before and after Brigade-1 using the Readiness for Inter-professional Learning Scale validated questionnaire. From these results, a modified version of the survey was developed that included quantitative and qualitative responses. For brigades-2 and -3, students received this modified version of the survey pre and post brigade. Quantitative data was analyzed via paired student t test, and qualitative data was analyzed to identify emerging themes using constant comparative methodology by three separate investigators. No significant quantitative differences between IP student groups were observed in their evaluation of the importance of inter-professional education either before or after the brigades. Qualitative data noted pre-brigade expectations of positive IP, experiential and patient-centered cultural learning. Pre- and post-brigade student perspectives maintained a strong belief that high functioning IP care benefited the patient. Post-brigade perspectives revealed a shift in attitude from purely positive expectations to more practical aspects of teamwork, respect, and interpersonal relationships. Students believe that patient care benefits from IP collaboration. After a busy clinical experience requiring collaboration, students realized that functional teams require appropriate skills, roles, and respectful interpersonal relationships.